Analysing the linkage between total factor productivity and tourism growth in Latin American countries - Panayiotis Tzeremes (Journal of Economics, Finance and Administrative Science, 2022)
Purpose - The study aims to investigate the nexus between total factor productivity and tourism growth in Latin American countries for time series data from 1995 to 2017. Design/methodology/approach - Using the extension of the Granger noncausality test in the nonlinear time-varying of Ajmiet al. (2015), the study points out the interconnectedness between the variables during the period. Findings - The study found nonlinear causality between the variables. Particularly, studying the conclusions for the time-varying Granger causality fashion, it can be noticed that the one-way causality from total factor productivity to tourism growth is obtained for Argentina, Bolivia, Brazil, Uruguay and Venezuela, while the vice versa is confirmed for Chile, Ecuador and Nicaragua. Lastly, the study dissected the plots of the curve causality. Practical implications - In view of the results, some crucial policy implications could be suggested, such as, under certain circumstances and as an exceptional case, the use of policy instruments such as targeted investment, marketing and the support of tourism organizations focused on driving a tourism-led-based productivity and/or tourism programs and projects. Originality/value - The current work is distinguished from the existing body of understanding in several substantial directions. This work explores, for the first time, the linkages between the total factor productivity index and tourism growth for Latin American countries. No single attempt has been known to investigate this interaction by using nonlinear causality, and this study determines the shape of the curve between the total factor productivity index and tourism growth for each country.
Keywords: O47; O54; Z31; Z32; 330; Total factor productivity; Tourism growth; Time-varying approach; Latin American countries